How Do Users Value a Network Expansion? Evidence from the Public Transit System in Singapore - Eric Fesselmeyer; Haoming Liu (Institute for the Study of Labor (IZA), 2016)
We estimate the network externality of a public transit system by examining the effects of its expansion on the housing market. Our results show that a major expansion of Singapore's Mass Rapid Transit (MRT) system increased the price of apartments within 0.5 km of a pre-expansion station by 1.6% to 2.1% relative to apartments that were further away from a station. Evaluated at the mean housing price, the expansion increased the value of pre-connected apartments by at least S386 million, which is equivalent to about 8% of the estimated S5 billion cost of the expansion.
Keywords: H4; R21; R42; H23; 330; public transportation; housing; network effects